Isu al-mujarrabat menurut perspektif qiyas al-shabah - Nik Mohd Sofa’urrahman Nik Mohd Rosdi,; Syed Mohd Jeffri Syed Jaafar,; Abdul Karim Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The issue of al-mujarrabat is one of the khilafiah issues which is hotly debated among religious scholars in Malaysia particularly. There are issues that are often disputed by some Muslim groups such as the issue of zikr which is not done by the Prophet Muhammad; for instance, zikr with the pronouncement of Allah with certain number, the issue of blowing on water after reciting a verse of al-Quran and others. This dispute or contention stems from total abuse. Qiyas al-Shabah is among the instruments in fiqh motion debate which is important in helping to elicit ‘illah from certain issues and nas. When certain issues are separated and studied, there will be a lack in each qiyas made by certain religious scholars. Each of the responded issues by the certain religious scholars will usually involve the process of qiyas indirectly. So, this Qiyas al-Shabah will organize, and correct the issues that had been evaluated by them, by putting on more accurate issues to be evaluated. This research is a qualitative study as it relates to the debate of a theory that will involve the study of data in the references of classical and contemporary books and subsequently implemented in an issue and case. As a result of the implementation of Qiyas al-Shabah into this issue, it is found that the point of view of those who reject it is due to a literal understanding of a hadith or athar.